2012
DOI: 10.1007/s10578-012-0307-0
|View full text |Cite
|
Sign up to set email alerts
|

Social Functioning in Youth with Anxiety Disorders: Association with Anxiety Severity and Outcomes from Cognitive-Behavioral Therapy

Abstract: Social functioning was assessed using the Child Behavior Checklist and Teacher Report Form for children with anxiety disorders who participated in a randomized clinical trial (N = 161, aged 7-14). Significant relationships were found between severity of children's principal anxiety disorder and most measures of social functioning, such that poorer social functioning was associated with more severe anxiety. Among youth who received cognitive-behavioral therapy (n = 111), significant associations were found betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 72 publications
0
38
0
Order By: Relevance
“…For example, Ginsburg et al (2011) found that lower severity of anxiety at baseline was associated with a greater response to treatment in the Child/ Adolescent Multimodal Study (CAMS; 488 youth aged 7-17 years). Additionally, anxiety severity has been positively associated with poorer social functioning (Settipani & Kendall, 2013) and somatic symptoms in youth (Ginsburg et al, 2006).…”
Section: Anxiety Severitymentioning
confidence: 99%
“…For example, Ginsburg et al (2011) found that lower severity of anxiety at baseline was associated with a greater response to treatment in the Child/ Adolescent Multimodal Study (CAMS; 488 youth aged 7-17 years). Additionally, anxiety severity has been positively associated with poorer social functioning (Settipani & Kendall, 2013) and somatic symptoms in youth (Ginsburg et al, 2006).…”
Section: Anxiety Severitymentioning
confidence: 99%
“…A motivational interviewing technique for preventing medication-induced weight gain in children with bipolar disorder, which could be helpful to some older children with less severe DD, was described in a case report [151]. One small 8-week study compared risperidone directly with aripiprazole in children with ASD and found no difference in weight over time [152]. However, a much larger observational study clearly suggested aripiprazole is associated with less weight gain in youth [153].…”
Section: Primary Obesity Preventionmentioning
confidence: 99%
“…As seen in Figure 2 both interventions lead to significant changes in BMI compared to the control groups, in part because the control groups, particularly in the pediatric population, show steady increases in BMI. There are also reports that adjunctive topiramate, zonisamide, amantadine, or sibutramine (no longer marketed due to cardiac concerns), may be useful in limiting antipsychotic-associated weight gain [159, 152, 160162]. It should be noted that all of these treatments typically lead to very modest weight loss of ~1–3 kg, rather than normalizing an individual’s weight status.…”
Section: Primary Obesity Preventionmentioning
confidence: 99%
“…As might be expected, families who are able to attend treatment sessions regularly and consistently implement the interventions at home tend to have the most favorable outcomes 39,40 . Families with sufficient resources tend to be able to follow-through more consistently.…”
Section: Clinical Decision Makingmentioning
confidence: 71%
“…Continued research on mechanisms of change and moderators of response is needed to inform treatment adaptations tailored to individual family needs. Strategies to improve parent’s and teacher’s implementation of behavior management approaches are especially important given the association between these factors and treatment outcome 39,40 . In addition, questions persist about optimal methods for combining and sequencing various behavioral treatment components as well as behavioral treatments and medication for individual children and families.…”
Section: Future Directionsmentioning
confidence: 99%